Guidelines for family life education - Andrews, Norma (Population Programme Unit, Ministry of Health, 1974)
This report deals with a Family Life Education Programme set up by the Government of Trinidad and Tobago in 1969 to improve the quality of life, and to educate the public on matters relating to family planning and family life. To this end, information on involving the community in planning a programme to meet the needs identified was given special attention. Methods of approach in dealing with some of the major problems are presented
Keywords: Health and Family Life Education